Merajut Kehidupan: Strategi Mata Pencaharian Perempuan Berbasis Kearifan Lokal dan Pengurangan Stres melalui Kerajinan Purun (Eleocharis dulcis) di Kalangan Perajin Perempuan di Pedesaan Lahan Gambut - Yunindyawati Yunindyawati; Eva Lidya; Ulfa Sevia Azni (Society, 2025)
This research is important because purun crafts have become a livelihood strategy for women to earn income that fulfills the family’s food needs based on local wisdom. In addition, making crafts from purun socially provides a space for women to meet and share stories, thus reducing stress. This research aims to examine the presence of female Purun (Eleocharis dulcis) artisans in villages around peatland, specifically investigating three key areas: gender-based division of labor, the role of Purun in livelihood strategies, and the social-psychological benefits of making Purun crafts, namely stress reduction. The method used is qualitative-descriptive. Data was collected through in-depth interviews, observation, and documentation. The research results show that in the production of purun crafts, there is a division of labor based on gender, where women are involved in crafting and household tasks. In contrast, men gather purun materials in the swamp areas. Women play an important role in earning income through Purun crafts, which are used to meet basic needs such as food and education. The activity of making purun crafts enhances the social cohesion of women in the community. This shows that Purun crafts are important in the economy, maintaining social cohesion within the community and the psychosocial health of women involved in Purun weaving.